PENINGKATAN PENDAPATAN UMKM SEKUPANG MELALUI PENGEMBANGAN SDM DI ERA DIGITAL - Haldy, Muhammad; Firiansyah, Iranda; Riswandi, Riswandi; Martiano, Vereki; Saputra, Asron (PUAN INDONESIA, 2025)
This community service activity focuses on developing the role of human resources (HR) in MSMEs in the digital era to increase the income of micro-enterprises in Sekupang District, Batam City. The main objective of this activity is to improve the capacity and competency of MSMEs' HR so they can adapt to technological developments and increasingly dynamic market competition. Through a series of intensive training sessions and mentoring, participants will be equipped with practical skills in digital management, including digital marketing, social media management, e-commerce utilization, and digital financial literacy. This training is designed to be practical and contextual, tailored to the needs and characteristics of local MSMEs. After participating in this program, MSMEs are expected to be able to optimize digital technology to market their products, reach a wider consumer base, and manage their business finances efficiently. By improving the quality of human resources, business productivity and competitiveness will increase, ultimately impacting revenue growth and business sustainability. This activity also represents a tangible contribution from universities to fostering local community economic empowerment.